Developing scientific, transformational, eloquent, artistic, mathematical, mechanical, emotional, relational, and social talents through problem solving: A conceptual, practical, evidence-based analysis. (May 2023) - Maker, C June; Pease, Randy; Zimmerman, Robert H
Building on the definition of steamers (a tasty hot milk-infused drink), we defined STEAMMERS as "a blend of diverse talents, going beyond domain-specific to domain-integrated abilities. Like steamers, they have a rich and colorful 'flavor'!" They are passionate about solving problems they and others face by honoring and blending diverse perspectives and disciplines. Gifted children and young people have the potential to become STEAMMERS, making outstanding contributions to themselves, their communities, and their world. The underlying principle is to design learning experiences beyond traditional conceptions of STEM, STEAM, and other similar combinations of disciplines in ways that uncover, ignite, cultivate, and extend these potentials. Using Real Engagement in Active Problem Solving (REAPS), an evidence-based teaching model, enables educators to recognize, cultivate, and extend the talents of the STEAMMERS we need for our future. Here, we present our new concept, describe practices, and give evidence showing how it accomplishes these purposes.